Japan's wartime medical atrocities : comparative inquiries in science, history, and ethics - Nie, Jing-Bao, 1962- (Asia's transformations., 2010)
This volume brings together the contributions of a group of scholars from different countries and various academic disciplines. It examines Japan's wartime medical atrocities and their postwar aftermath from a comparative perspective and inquires into perennial issues of historical memory, science, politics, society and ethics elicited by these rebarbative events. The volume's central ethical claim is that the failure to bring justice to bear on the systematic abuse of medical research by Japanese military medical personnel more than six decades ago has had a profoundly retarding influence on the development and practice of medical and social ethics in all of East Asia. The book alsom includes an extensive annotated bibliography selected from relevant publications in Japanese, Chinese and English. --Book Jacket.